Carinthian Enthronization Ceremony and the Premyslid Myth (Theatrum historiae, 2019)
The present study deals with the medieval enthronization ceremony held in Zollfeld near Karnburg where the Carinthian dukes were inaugurated. This ceremony was described in a number of period sources from the 13th to the 15th centuries (the last ritual took place in 1414) and has been explored by many scholars since the end of the 19th century to the present. At the same time, the literature sources point to a cultural connection with similar rites known from both Slavic and Indo-European environments. One of the aims of the study is therefore to summarize and point to the most significant existing theories concerning the origin and the course of the ceremony. Another aim is to point out the connection between Carinthian setting ritual and a legend (or myth) about the origin of princely power in Bohemia where a similar ritual, apparently inspired by this myth, was proved in the early modern period. In the end, the study, in accordance with the current research, attempts to suggest a possible interpretation of the individual elements that are a part of both the setting ceremony and the myth of the royal power.
Keywords: Carinthia; enthronization ceremony; Premyslid myth; archaic culture; Slavs